2007
DOI: 10.2478/v10004-007-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiofrequency Electromagnetic Fields on Mammalian Spermatogenesis

Abstract: This article reviews studies about the effects of radiofrequency electromagnetic (RF EM) fields on male reproductive system and reproductive health in mammals. According to current data, there are almost 4 million active mobile phone lines in Croatia while this number has risen to 2 billion in the world. Increased use of mobile technology raises scientific and public concern about possible hazardous effects of RF fields on human health. The effects of radiofrequencies on reproductive health and consequences fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…The implementation of ray-tracing in START is basically the same as that adopted in RSPH, which has been used for simulations of structure formation in the early Universe (Susa & Umemura 2006;Susa 2007Susa , 2008). Since the rays are cast from all radiation sources to all SPH particles, the RSPH scheme allows us to solve RHD problems very accurately (Iliev et al 2006a;Susa 2006;Iliev et al 2009). Moreover, this ray-tracing algorithm enables us to solve RT without losing the spatial resolution of hydrodynamics calculation, since SPH particles are directly used for RT grids.…”
Section: Uv Feedbackmentioning
confidence: 99%
“…The implementation of ray-tracing in START is basically the same as that adopted in RSPH, which has been used for simulations of structure formation in the early Universe (Susa & Umemura 2006;Susa 2007Susa , 2008). Since the rays are cast from all radiation sources to all SPH particles, the RSPH scheme allows us to solve RHD problems very accurately (Iliev et al 2006a;Susa 2006;Iliev et al 2009). Moreover, this ray-tracing algorithm enables us to solve RT without losing the spatial resolution of hydrodynamics calculation, since SPH particles are directly used for RT grids.…”
Section: Uv Feedbackmentioning
confidence: 99%
“…Even though a considerable number of epidemiological, in vivo and in vitro studies have been conducted to provide scientific evidence for a health risk assessment of mobile phone radiation [22, 23], apart from our group's recent papers no reports regarding the biological effects of exposure to multiple RF radiation signals are available. We reported that combined exposure of CDMA and WCDMA RF radiation did not cause any observable adverse effects on mouse fetuses [24].…”
Section: Discussionmentioning
confidence: 99%
“…We perform numerical simulations with the radiation hydrodynamics code that we developed (Susa 2006). In this section, we briefly summarize the scheme.…”
Section: Methodsmentioning
confidence: 99%